"Valoración sensorial de la carne del pez nativo vieja colorada (Cichlasoma festue L.) alimentada con torta de palmiste (Elaeis Guineensis Jacq) en el cantón Quevedo" - Buenaño Álvarez, Josúe Alexander (2017)
The present investigation was carried out in the State Technical University of Quevedo, with the objective of making a sensory evaluation of the meat of old red fish (Cichlasoma festae L.) that was fed with palm kernel cake during its stage of fattening 1, in the which was fed to the fish 4 times a day for 30 days, 4 treatments and 3 repetitions were used, using a nonparametric analysis of Kruskall and Wallis with a (5%) probability. The treatments consisted of T1 as a control, having (0%) of palm kernel cake, T2 with (4%), T3 with (8%) and T4 with (12%) of palm kernel cake. For the sensory analysis the variables of appearance, texture, smell and taste were evaluated. A feeding cost analysis was also carried out to determine the synergy of the treatment with better organoleptic qualities and with the best price. The results of this research work were encouraging giving T3 as the best treatment, which stood out in flavor (with a 2.36 average rating) and with a feed cost of $ 0.969 per fish. Key Words: Palm kernel cake, Cichlasoma festae, feeding cost, sensory evaluation.